From Feminism to Revolution: A Study of the Shanghai Young Women’s Christian Association During the War of Resistance - JIN, Lujie (Journal of Research for Christianity in China (JRCC), 2025)
Following the outbreak of the War of Resistance Against Japan, the Communist Party of China adjusted its guiding principles and policies for underground activities in Shanghai to adapt to the new situation. Influenced by the underground Communist Party’s operations, revolutionary tendencies gradually emerged within the Shanghai Young Women’s Christian Association (YWCA). The YWCA, originally a non-partisan women’s organization, increasingly leaned toward sympathizing with the Communist Party and even engaging in activities supporting it. This paper traces the Communist Party’s revolutionary activities within the Shanghai Young Women’s Christian Association during the War of Resistance by examining the circumstances of undercover Party members within the association and the underground Party activities emerging in its affiliated undertakings. It concludes with an in-depth analysis of the unique role the Shanghai Young Women’s Christian Association played as a gathering place for numerous underground Party members. The association’s revolutionary tendencies were linked to the activities of these underground members and also represented its choice to accelerate its localization.